Challenges of urban garden initiatives for food security in Kuala Lumpur, Malaysia - Ishak, Norziha; Abdullah, Rosazlin; Mohd Rosli, Noor Sharina; Majid, Hazreen Abdul; Halim, Nur Sa’Adah Abdul; Ariffin, Fazilah (Quaestiones Geographicae, 2022)
Sustainable urban farming is a strategy to improve food availability and food access, and to support food security for the urban population in Malaysia. However, the development of these activities has been affected by several constraints. This article aims to identify the challenges faced by urban farmers in Kuala Lumpur. The challenges of practicing urban gardening were categorised into five groups (technical, resource-related, economic, social and environmental factors). Data were collected via a questionnaire survey distributed to 106 urban farming practitioners from 17 urban gardens in Kuala Lumpur and were analysed using descriptive analysis by tabulating the frequency and percentage. The result showed that highly fluctuating weather, problems with access to available land and financial problems were the main challenges faced by urban farmers in Kuala Lumpur. Furthermore, difficulty in access to a financial institution, lack of commitment and the increased number of pests were also the problems faced by the urban garden. Availability of technical factors is the least issue in this study. Correlation analysis was used to determine the relationship between the challenges of urban gardens and socio-demographics. The result showed that there was a weak correlation between technical factors of educational level (r = 0.225) and race (r = 0.210), respectively, as well as between race and social factor (r = 0.201), while there was a moderate correlation between age and environment factor (r = −0.410). There is a need for further work, and comprehensive research should be conducted to capture what actions can be taken to create a policy-making space for urban farmers.